Perlindungan Hukum Terhadap Penyewa Halaman Rumah Atas Ingkar Janji Mu’jir - Sihite, Sri Rumada (PAMALI: Pattimura Magister Law Review, 2024)
Introduction: The broken promise made by the owner of the vacant land rented by mei symbolon which has an impact on material losses, which has legal consequences for the legal actions taken by the landowner, Mr. x, of course this is the background for the author to explain the problem and explain the legal protection of the tenant of the house yard for the broken promise of the mu'jir.Purposes of the Research: Reviewing what rights are received by the party that must be received if the agreement between them is made by a unilateral promise and what obligations must be fulfilled by the owner of the house yard for legal actions that make a promise break.Methods of the Research: The research method used is normative juridical method with statutory and conceptual approaches.Results of the Research: The agreement that gave birth to the binding between the tenant of the yard and the owner of the yard is valid and fulfills the principle of consensualism and of course this has legal consequences where there are rights and obligations of each. In this case the non-fulfillment of the obligations of the owner of the empty courtyard, namely reselling the house and the empty courtyard which in the civil law code is a breach of promise, of course this is required by the owner of the yard to compensate for the loss as written.